PERAN PONDOK PESANTREN DALAM MENINGKATKAN MORALITAS KEAGAMAAN DI LINGKUNGAN BANJAR (STUDI KASUS PONDOK PESANTREN NURUL JANNAH NW AMPENAN) - IDRIS SARDI (Universitas Mahasaraswati K. Mataram, 2024)
This research is field research with a qualitative case study type approach. Data collection was carried out using participatory observation techniques, interviews and documentation. The intensive research process was carried out for almost seven months involving competent informants from the Islamic boarding school and community leaders in the Banjar area. Religious activities are one of the efforts to shape the religious morality of the people of the Banjar area, so that the people have Islamic and virtuous morals. In this case, religious activities in the form of TPQ, Hiziban, Sayafaah, Public Study, Hadroh, PHBI emphasize the involvement of the Banjar Neighborhood community in carrying out active religious activities so that the community can receive direct and trained training to be able to carry out the religious activities they participate in themselves. Therefore, one of the benefits of religious activities is to form individuals with Islamic morals and dignity. Thus, through religious activities it is hoped that it can improve the religious morality of the people of the Banjar EnvironmentThis research concludes that improving the religious morality of the people of the Banjar Environment through religious activities carried out by the Nurul Jannah NW Ampenan Islamic Boarding School, including TPQ, Hiziban, Sayafaah, Public Recitation, Hadroh, and PHBI